Assessment of the strength of double-hull tanker side structures in minor ship collisions. (1st August 2016) - Liu, Bin; Guedes Soares, C.
Highlights: An analytical method is presented to examine the energy absorbed in a double-hull subjected to a flat indenter. A numerical simulation is conducted on a structural module derived from an experimentally scaled stiffened panel. The numerical definition of material nonlinearities for the selected mesh size is validated against previous experiments. The analytical method gives good agreement with the corresponding numerical force–displacement response. The analytical method of internal mechanics is combined with the theoretical analysis of external dynamics. Abstract: The paper presents a simplified analytical method to examine the energy absorbing mechanisms of double-hull ship structures subjected to a flat edge indenter. To validate this method, a numerical simulation is conducted on a structural module derived from an experimentally scaled stiffened panel in previous work. The structural module represents one-fifth scaled double-hull tanker side structures, including three frame spacings along the longitudinal direction and two stringer spacings along the vertical direction. The paper provides practical information to estimate the extent of structural damage within double-hull tanker side structures during minor head-on collisions, where the inner hull does not participate in absorbing impact energy. The numerical definition of material nonlinearities for the selected mesh size is validated against previous experimental results. The numerical simulation describes the plastic deformation and material rupture in the double-hull structure and provides detailed information of the energy dissipated by each structural component. The simplified analytical method estimates the relation between the plastic deformation and the crushing force of the double-hull structure, giving a good agreement with the corresponding numerical force–displacement response. Moreover, the analytical method of internal mechanics is combined with a theoretical analysis of external dynamics to evaluate the energy absorption in a ship-to-ship collision. A procedure for assessing the strength of a collided ship is presented on the basis of the experiments of scaled structures.